Method for producing long fiber composite material

By using mathematical formula to control the penetration process of non-Newtonian resins, the problem of low penetration efficiency in thermoplastic long fiber composites is solved, and efficient impregnation process and production efficiency are improved.

CN114423592BActive Publication Date: 2025-04-04SOONCHUNYANG UNIV IND ACAD COOP FOUND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080065812.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-18
Filing Date
2020-07-16
Publication Date
2025-04-04
Estimated Expiration
2040-07-16

AI Technical Summary

Technical Problem

Prior Art In the manufacture of thermoplastic long fiber composites, the high viscosity of non-Newtonian resins leads to a longer impregnation time, reduces production efficiency, and makes it difficult to effectively penetrate the resin into the fiber bundle.

Method used

By using the mathematical formulas that represent the permeability pressure, effective viscosity, vertical permeability and average permeability rate of the non-Newtonian resin and the thickness of the fiber bundle, the impregnation process is controlled to improve the permeability efficiency of the non-Newtonian resin.

Benefits of technology

The prediction of impregnation and processing conditions are achieved to ensure that the impregnation of the resin is fully realized within a predetermined time, simplifying the process flow and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114423592B_ABST
    Figure CN114423592B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a long fiber composite material in which a non-Newtonian resin is impregnated in a fiber bundle; and to a method for manufacturing a thermoplastic long fiber composite material, wherein the method improves the efficiency of the non-Newtonian resin impregnation process by utilizing a mathematical formula 1 representing the correlation between the penetration pressure, effective viscosity, vertical permeability and average penetration velocity of the non-Newtonian resin and the thickness of the fiber bundle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a long fiber composite material, and more particularly to a method for producing a long fiber composite material in which a fiber bundle is impregnated with a resin.

[0002] Furthermore, the present invention relates to a method for producing a thermoplastic long-fiber composite material in which a fiber bundle is impregnated with a non-Newtonian resin.

[0003] In addition, the present invention relates to a method for manufacturing a thermoplastic long fiber composite material, which improves the efficiency of the non-Newtonian resin impregnation process by utilizing Mathematical Formula 1 representing the correlation between the penetration pressure, effective viscosity, vertical permeability and average penetration velocity of the non-Newtonian resin and the thickness of the fiber bundle. Background Art

[0004] As the demand for high-rigidity and lightweight materials in the industrial field increases due to high oil prices, attention to continuous fiber-reinforced polymer composites is increasing. As for thermosetting resins, since they have low viscosity, the impregnation degree of intermediate materials and finished products is excellent, and mass production can be carried out at a faster impregnation speed, so a lot of research and product production have been carried out in the past. However, it has the disadvantages of difficult recycling and long resin curing cycle. On the contrary, as global attention to environmental protection increases and it becomes urgent to ensure price competitiveness based on the global market, attention to thermoplastic polymer composites with the advantages of recyclability and shortened process time has become more focused. However, as for thermoplastic resins, since their melt viscosity is very high, the time required for impregnation increases, thereby reducing productivity, so it is inevitable to consider the loss of product price competitiveness.

[0005] Among thermoplastic resin polymer composites, the production of products using short fiber reinforced thermoplastic polymer composites (SFT) and long fiber reinforced thermoplastic polymer composites (LFT) constitutes a large part in the industry. However, with the change of market preferences that consider higher levels of high rigidity, light weight, price competitiveness and environmental protection at the same time, the preference for continuous fiber reinforced thermoplastic polymer composites (Contous fiber reinforced thermoplastic) has increased, and increasing productivity by improving its manufacturing process efficiency is becoming a major focus.

[0006] On the other hand, the process of attaching resin to fiber bundles and permeating the fiber bundles is called impregnation process. It is extremely difficult to produce resin-impregnated fiber bundles that reach the desired production time by simply attaching resin and expecting permeation through capillary phenomena. Therefore, research is being conducted to improve the impregnation of resin into the fiber bundles.

[0007] As a prior art, Japanese Patent Publication No. Sho 60-240435 discloses a method for producing a resin-impregnated fiber bundle by maintaining all production equipment in a reduced pressure space. Summary of the invention

[0008] Problems to be solved by the invention

[0009] An object of the present invention is to provide a method for producing a long-fiber composite material in which a fiber bundle is impregnated with a resin.

[0010] In addition, the present invention relates to a method for manufacturing a thermoplastic long fiber composite material, which improves the efficiency of the non-Newtonian resin impregnation process by utilizing Mathematical Formula 1 representing the correlation between the penetration pressure, effective viscosity, vertical permeability and average penetration velocity of the non-Newtonian resin and the thickness of the fiber bundle.

[0011] Solutions for solving problems

[0012] In order to achieve the above object, the present invention provides a method for producing a long fiber composite material.

[0013] The above-mentioned manufacturing method uses a manufacturing device for long-fiber composite materials, which includes: a container for containing resin; a roller, which is arranged inside the above-mentioned container and rotates in one direction; a lead-out part, which is used to apply tension to the fiber bundle and move the above-mentioned fiber bundle in one direction; and a resin supply part, which supplies resin into the above-mentioned container.

[0014] The above manufacturing method is characterized by comprising:

[0015] a supplying step, wherein the resin supplying part supplies the resin into the container at a preset pressure;

[0016] a moving step, wherein the lead-out portion moves the fiber bundle in one direction;

[0017] The impregnation step is to allow the resin supplied to the interior of the container to penetrate into the interior of the fiber bundle.

[0018] The above-mentioned impregnation step is controlled according to the following mathematical formula 1.

[0019]

Mathematical formula 1

[0020]

[0021] V o : Average penetration velocity of fiber bundle, n: Power law coefficient of resin, K y : Vertical permeability, μ eff : effective viscosity, ΔP: penetration pressure of resin, L: thickness of fiber bundle.

[0022] Effects of the Invention

[0023] The manufacturing method of the present invention can predict in advance the impregnation degree according to processing conditions such as the type and processing form of the fiber bundle and the type of resin, so the processing conditions of the fiber bundle and the resin can be set so that complete impregnation is achieved within a predetermined time.

[0024] In addition, a relatively simple process method, that is, a method of controlling the supply pressure of the resin or the porosity of the fiber bundle, can improve the impregnation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram showing a part of a manufacturing device of a long fiber composite material according to an embodiment of the present invention.

[0026] Figure 2 and Figure 3 FIG. 4 is a schematic diagram showing a fiber unit according to an embodiment of the present invention.

[0027] Figure 4 is an algorithm representing a method for manufacturing a long fiber composite material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] Hereinafter, the preferred embodiments of the present invention will be described as follows with reference to the accompanying drawings. However, the embodiments of the present invention may be modified in various other forms, and the scope of the present invention is not limited to the embodiments described below. In addition, the embodiments of the present invention are provided in order to more completely describe the present invention to those of ordinary skill in the art. Therefore, in order to explain more clearly, the shapes and sizes of the elements in the drawings may be exaggerated, and the elements represented by the same reference numerals in the drawings are the same elements. In addition, for parts with similar functions and effects, the same reference numerals are used throughout the drawings. In addition, "comprising" a certain component element throughout the specification, unless otherwise explicitly stated, means that other components may be further included, rather than excluding other components.

[0029] The method for manufacturing a long fiber composite material according to an embodiment of the present invention is a method for manufacturing a long fiber composite material formed by impregnating a resin into a fiber bundle, and in particular, it can be a method for manufacturing a long fiber composite material by impregnating a thermoplastic resin having a heating and melting property into a fiber bundle.

[0030] Therefore, the long fiber composite material according to the embodiment of the present invention may be a thermoplastic long fiber composite material.

[0031] The term "fiber bundle" as used herein refers to a fiber bundle consisting of hundreds to tens of thousands of fibers having an average diameter (D) of several to tens of micrometers (μm). f ) is a fiber bundle formed by bundling fiber units.

[0032] The fiber bundle may be at least one of glass fiber filaments, carbon fiber filaments, basalt fiber filaments, aramid fiber filaments, spectrum fiber filaments, natural fiber filaments, and mixed filaments thereof.

[0033] According to the method for manufacturing a long fiber composite material according to an embodiment of the present invention, the method for manufacturing a long fiber composite material uses a device for manufacturing a long fiber composite material.

[0034] The manufacturing device of the above-mentioned long fiber composite material includes: a container, which is used to hold resin; a roller, which is arranged inside the above-mentioned container and rotates in one direction; a lead-out part, which is used to apply tension to the fiber bundle and move the above-mentioned fiber bundle in one direction; and a resin supply part, which supplies resin into the inside of the above-mentioned container.

[0035] The manufacturing method comprises:

[0036] a supplying step, wherein the resin supplying part supplies the resin into the container at a preset pressure;

[0037] a moving step, wherein the lead-out portion moves the fiber bundle in one direction;

[0038] The impregnation step is to allow the resin supplied to the inside of the container to permeate into the inside of the fiber bundle. The impregnation step can be controlled according to the following mathematical formula 1.

[0039] [Mathematical formula 1]

[0040]

[0041] V o : Average penetration velocity of fiber bundle, n: Power law coefficient of resin, K y : Vertical permeability, μ eff: effective viscosity, ΔP: penetration pressure of resin, L: thickness of fiber bundle.

[0042] Figure 1 FIG. 1 is a schematic diagram showing a part of a manufacturing device for a long fiber composite material according to an embodiment of the present invention. Figure 1 As shown, a manufacturing device for a long fiber composite material according to an embodiment of the present invention may include: a container 10, which is used to hold resin; a roller 20, which is arranged inside the above-mentioned container and rotates in one direction; a lead-out portion 30, which is used to apply tension to the fiber bundle 200 and move the above-mentioned fiber bundle 200 in one direction; and a resin supply portion 40, which supplies the resin 100 to the inside of the above-mentioned container.

[0043] Hereinafter, the method for manufacturing a long fiber composite material according to an embodiment of the present invention will be described in detail step by step.

[0044] The supplying step is a step in which the resin supply part 40 supplies the resin 100 into the container 10 at a preset pressure.

[0045] like Figure 1 As shown, the container 10 may be a container with its upper and lower parts open, which is connected to the resin supply part 40, receives the resin from the resin supply part 40, and infiltrates the received resin into the fiber bundle.

[0046] like Figure 1 As shown, the resin supply part 40 is connected to the inlet of the container 10 having a narrow inlet at the lower portion, and the resin 100 can be supplied into the container through the inlet.

[0047] At this time, the resin supply unit 40 may preferably supply the resin 100 into the container 10 at a pressure of 0.3 to 5.5 atm.

[0048] This is to allow the resin 100 to penetrate into the interior of the fiber bundle 200. If the pressure is less than 0.3 atm, the resin may not be able to penetrate into the interior of the fiber bundle. If the pressure exceeds 5.5 atm, the fiber bundle may be difficult to move during the resin penetration process.

[0049] The resin 100 may be at least one of a thermoplastic resin, a thermoplastic resin exhibiting thermoplastic properties at 50 to 500° C., a non-Newtonian resin, a power-law non-Newtonian resin exhibiting power-law non-Newtonian properties at room temperature, and a mixture thereof.

[0050] The resin 100 may be a non-Newtonian resin having a power law coefficient of 0.25 to 0.92.

[0051] Among them, non-Newtonian resin refers to a resin having non-Newtonian properties, that is, a property that the viscosity changes according to the shear rate, which can be the same as non-Newtonian fluids. For Newtonian fluids, the properties or flow of the fluid remain constant regardless of the external load, and the viscosity can be expressed only as a function of temperature and pressure. Such Newtonian fluids can be fluids having the property that the viscosity remains constant even when the shear rate changes.

[0052] The non-Newtonian resin may be a power-law non-Newtonian resin.

[0053] The power-law non-Newtonian resin may refer to a non-Newtonian resin in which the viscosity of the resin according to the shear rate is represented by the parameters of the power-law coefficient and the zero shear rate viscosity.

[0054] Most polymer plastic resins exhibit shear thinning, that is, as the shear rate increases, the viscosity of the resin decreases. The power law coefficient is an indicator that quantifies the shear thinning phenomenon as described above, and has a value between 0 and 1. At this time, the more severe the reduction in resin viscosity is compared with the shear rate, the closer it is to 0; conversely, the weaker the reduction in resin viscosity is compared with the shear rate, the closer it is to 1. For example, the power law coefficient of polypropylene resin with severe shear thinning is around 0.3 to 0.4, and the power law coefficient of polycarbonate resin with weak shear thinning is around 0.9.

[0055] The non-Newtonian resin is a non-Newtonian resin having affinity with the surface of the fiber bundle, and may include at least one of maleic anhydride, acrylic acid, amine, ester, epoxy and chemically bonded compounds thereof.

[0056] In addition, the above-mentioned non-Newtonian resin is a non-Newtonian resin that shows affinity with the surface of the fiber bundle, and may include at least one of polypropylene resin, nylon resin, polyethylene resin, polybutylene terephthalate resin, polyethylene terephthalate resin, polyvinyl chloride resin and mixed resins thereof.

[0057] The polypropylene resin may include at least one of homopolypropylene, propylene-ethylene block copolymer polypropylene, propylene-ethylene random copolymer polypropylene and metallocene polypropylene, preferably including 40 wt % or more.

[0058] The polyethylene resin may include at least one of high-density polyethylene, low-density polyethylene, linear low-density polyethylene, metallocene polyethylene and ethylene elastomer, and preferably includes 40% by weight or more.

[0059] The nylon resin is a resin containing an amide component group, and may be at least one of nylon 6, nylon 66, nylon 12, nylon 46, polyphthalamide, amorphous nylon, and mixed resins thereof.

[0060] The moving step is a step in which the lead-out unit 30 moves the fiber bundle 200 in one direction.

[0061] In the method for manufacturing a long fiber composite material according to the embodiment of the present invention, the fiber bundle 200 is moved in one direction or in two directions, and the resin is infiltrated into the fiber bundle 200 .

[0062] In the above fiber bundle 200, the distance from one side to the other side of the fiber bundle 200 is called thickness; in the above, the distance from one end to the other end of the fiber bundle in a direction perpendicular to the moving direction of the fiber bundle 200 is called width; and the distance from one end to the other end of the fiber bundle in a direction parallel to the moving direction of the fiber bundle 200 is called length. Figure 2 and Figure 3 As shown, the fiber bundle 200 may include Figure 2 As shown, the fiber bundle 200 may include a plurality of fiber units arranged in the width direction, or may include a plurality of fiber units arranged in the length direction. While the fiber bundle 200 moves in the length direction, the resin 100 may penetrate in the thickness direction of the fiber bundle 200.

[0063] The lead-out portion 30 may apply tension to the fiber bundle 200 to move the fiber bundle 200 in one direction, and the tension may be applied in the direction in which the fiber bundle moves through the lead-out portion.

[0064] The impregnation step is a step of allowing the resin supplied to the interior of the container to permeate into the interior of the fiber bundle.

[0065] The impregnation step may be a step of filling the pores of the fiber bundle 200 with the resin 100 .

[0066] The fiber bundle 200 includes pores between the plurality of fiber units, and thus may have porosity. Therefore, the fiber bundle may be a fiber porous medium having a plurality of pores therein, and the impregnation step may be a step of allowing the resin 100 to penetrate into the fiber bundle to fill the pores of the fiber bundle 200.

[0067] The above-mentioned impregnation step can be controlled according to the following Mathematical Formula 1.

[0068] [Mathematical formula 1]

[0069]

[0070] V o : Average penetration velocity of fiber bundle, n: Power law coefficient of resin, K y : Vertical permeability, μ eff : effective viscosity, ΔP: penetration pressure of resin, L: thickness of fiber bundle.

[0071] The above mathematical formula 1 represents the penetration pressure ΔP and effective viscosity μ of the resin. eff , vertical permeability K y and the average penetration velocity V o , the correlation between the fiber bundle thickness L.

[0072] At this time, the resin may preferably be a thermoplastic resin, a non-Newtonian resin, or a non-Newtonian fluid having an effective viscosity.

[0073] The effective viscosity is a viscosity represented by a power law coefficient representing a shear thinning phenomenon of a thermoplastic resin, a non-Newtonian resin or a non-Newtonian fluid, and can be calculated according to the following Mathematical Formula 2.

[0074] [Mathematical formula 2]

[0075]

[0076]

[0077] μ0: zero shear rate viscosity of the resin, Φ max / Φ: relative volume fraction of fiber bundles, Custom parameters.

[0078] The above impregnation step can be performed according to Figure 4 algorithm control. Figure 4 The algorithm can be carried out as follows:

[0079] Figure 4 is an algorithm representing a method for manufacturing a long fiber composite material according to an embodiment of the present invention.

[0080] First, in the first step, the diameter D of the fiber unit included in the fiber bundle is set. f , number and width of the fiber bundle, select the type of resin, set the zero shear rate viscosity μ0, the power law coefficient n, and the resin penetration pressure ΔP as the processing condition.

[0081] At this time, the diameter D of the fiber unit f It may preferably have a size of 5 to 100 μm.

[0082] If, when the diameter D of the above fiber unit f When the diameter D of the fiber unit is less than 5 μm, the impregnation property may be reduced in the step of impregnating the long fiber containing the fiber unit. f When it exceeds 100 μm, there may occur a problem that the mechanical properties of the final product, ie, the long fiber composite material, are deteriorated.

[0083] The width of the fiber bundle is preferably 10 to 30 mm, more preferably 12 to 24 mm.

[0084] If the width of the fiber bundle is less than 10 mm, it may be difficult to impregnate the resin. If the width of the fiber bundle exceeds 30 mm, excessive friction may occur due to the speed difference between the fiber units.

[0085] Zero shear rate viscosity refers to the viscosity of the resin when the shear rate is 0.

[0086] The above resin may be a non-Newtonian resin having a zero shear rate viscosity of 1 to 300 Pa·s.

[0087] If the zero shear rate viscosity is less than 1 Pa·s, the problem of reduced mechanical properties due to too low molecular weight may occur; when the zero shear rate viscosity exceeds 300 Pa·s, the problem of difficult resin impregnation may occur due to too high viscosity.

[0088] Furthermore, the above resin is preferably a non-Newtonian resin having a power-law coefficient of 0.25 to 0.92.

[0089] If the power law coefficient is less than 0.25, it is difficult to design the polymer and there may be a problem that additives for improving fluidity, such as plasticizers, need to be excessively mixed; and when the power law coefficient exceeds 0.92, there may be a problem that the resin is difficult to penetrate.

[0090] Furthermore, the permeation pressure ΔP of the above resin may preferably be 0.3 to 5.5 atm.

[0091] If, when the penetration pressure ΔP of the above-mentioned resin is less than 0.3atm, the problem that the above-mentioned resin has difficulty in penetrating into the above-mentioned fiber bundle may occur; when the penetration pressure (ΔP) of the above-mentioned resin exceeds 5.5, the problem that excessive force is applied to the above-mentioned fiber bundle during the penetration process of the above-mentioned resin may occur, making it difficult to move.

[0092] The second step is to set the porosity of the fiber bundle under the above-mentioned conditions.

[0093] The above-mentioned porosity may have a value of 0.1 to 0.9, but is not limited thereto.

[0094] The impregnation step according to an embodiment of the present invention may include a porosity control step, which controls the porosity of the fiber bundle so that the penetration time required for the resin 100 to fill the internal pores of the fiber bundle 200 is below a preset value.

[0095] The porosity can be calculated according to the following <Formula 1>.

[0096] The porosity may have a value between 0 and 1, and more preferably, may have a value between 0.1 and 0.9.

[0097] The fiber volume fraction Φ occupied by a fiber unit in a fiber bundle may be (1-porosity).

[0098] [Formula 1]

[0099]

[0100] The porosity can be different depending on the fiber volume content, the distance between fiber units, and the packing form of the fiber units. Long fiber composites can be manufactured with high fiber content, and the fiber units can be packed into a hexagonal form.

[0101] In addition, the distance S between the fiber units can be calculated according to the following <Formula 2>, and if, when the above fiber units are filled into a hexagon, the aspect ratio (Aspect ratio, S) between the fiber units f ) can be √3.

[0102] [Formula 2]

[0103]

[0104] S: distance between fiber units, S f : aspect ratio between fiber units, Φ: fiber volume fraction, D f : The diameter of the fiber unit.

[0105] The number of fiber units included in the fiber bundle can be calculated according to the following <Formula 3>.

[0106] [Formula 3]

[0107]

[0108] TEX: weight in grams per 1 km of fiber bundle.

[0109] Weight of fiber unit per 1m = cross-sectional area of ​​fiber unit × fiber density

[0110]

[0111] The fiber bundle can know the number of fiber units contained in a layer in the unfolded width W when the fiber bundle is unfolded according to the fiber volume content by the number of fiber units contained in the fiber bundle and the distance s between the fiber units calculated according to the above formula 3, and the number of fiber unit layers contained in the above fiber bundle can be known from the number of fiber units existing in a layer. In this way, if the number of fiber unit layers of the fiber bundle is known, the thickness L that the resin should penetrate can be known.

[0112] At this time, the penetration time may be the time required to fill all the pores inside the fiber bundle or the time required to reduce the porosity of the fiber bundle to 0%, that is, the complete penetration time.

[0113] The porosity of the fiber bundle can refer to the volume fraction of the pores in the fiber bundle. Therefore, when the fiber volume fraction occupied by the fiber unit in the fiber bundle is called When the porosity is The value of .

[0114] For example, if in the above fiber bundle, the volume content of the fiber unit is 40%, the fiber volume fraction is 0.4 and the porosity may be 0.6.

[0115] When the penetration time is within 8 seconds, it can be regarded as a reference time for designing an impregnation mold. Therefore, the preset time is preferably within 8 seconds, more preferably within 7 seconds, and further preferably within 6 seconds.

[0116] The reference time for designing the impregnation mold may be a time that allows continuous production, that is, a time that is not uneconomical due to slow flux of the fiber bundle, a long residence time in the mold, and does not hinder the stability of the resin. The reference time for designing the impregnation mold may be different depending on the flow of the fiber bundle and the length of the impregnation mold.

[0117] When the resin is infiltrated into the fiber bundle, if the impregnation mold is lengthened to extend the contact time between the fiber bundle and the resin, it is beneficial to the impregnation, but a problem may occur that a large force is required to move the fiber bundle. Therefore, the above-mentioned infiltration time can be adjusted according to the design of the impregnation mold. Therefore, the design of the above-mentioned impregnation mold should allow the resin to be completely impregnated into the above-mentioned fiber bundle in the shortest possible time. As an example, when the flow of the fiber bundle moves at 10m / min and passes through the impregnation mold of 1m in length, it is in contact with the resin for about 6 seconds, and resin penetration can occur.

[0118] If the flow of the fiber bundle moves slower than 10 m / min, it may be unfavorable for mass production and lead to reduced manufacturing productivity; when the length of the impregnation mold exceeds 1 m, the load applied to the fiber bundle during movement is too high, which may cause difficulty in continuous production.

[0119] The porosity control step may include controlling a distance between each fiber unit included in the fiber bundle 200 .

[0120] The step of controlling the distance between each fiber unit included in the fiber bundle may be performed by applying a force to the fiber bundle in a direction perpendicular to a direction in which the tension is applied.

[0121] Since the direction in which the tension is applied is parallel to the moving direction, the direction in which the force is applied to the fiber bundle may be perpendicular to the moving direction.

[0122] For example, by applying a force in a direction perpendicular to the direction in which the tension is applied, the distance between the plurality of fiber units arranged in the length direction can be increased.

[0123] At this time, the amount of resin in contact with the fiber bundle can be adjusted using the resin knife 50. By using the resin knife 50, the amount of resin in contact with the fiber bundle can be adjusted so that no excess resin surrounds the fiber bundle at the same time.

[0124] The resin knife refers to a device for skimming off the resin pulled up by the rotating roller, and may be a device for adjusting the amount of resin coated by the rotating roller, for example, a roller coating adjustment knife.

[0125] The long fiber composite material manufacturing device may further include a resin knife 50 located at the fiber bundle input portion of the first roller, and the resin knife 50 is used to adjust the amount of resin applied to the rotating roller 20, that is, to adjust the amount of resin permeated into the fiber bundle, so that the fiber units included in the unfolded fiber bundle 200 can be partially coated. By this, the partially coated fiber units can be separated more easily, so that the distance between the fiber units can be more easily adjusted.

[0126] The vertical direction in this specification is not limited to the direction at 90° to the reference direction, but may refer to all of the component vectors when there are component vectors with respect to the direction at 90° to the reference direction.

[0127] Furthermore, the parallel direction is not limited to the direction at an angle of 0° or 180° with respect to the reference direction, and may refer to all of the component vectors when there are component vectors at an angle of 0° or 180° with respect to the reference direction.

[0128] For example, the step of controlling the distance between the fiber units may be performed by applying force in a direction at an angle of 45° or 90° to the direction in which the tension is applied to the fiber bundle, or by applying force in the thickness direction of the fiber bundle.

[0129] In the third step, after calculating the distance S between each fiber unit in the fiber bundle having a specific porosity, the penetration rate V of the resin into the above fiber bundle is calculated based on the following mathematical formula 1: o , from which the penetration time of the above resin can be calculated.

[0130] [Mathematical formula 1]

[0131]

[0132] V o : Average penetration velocity of fiber bundle, n: Power law coefficient of resin, K y : Vertical permeability, μ eff : effective viscosity, ΔP: penetration pressure of resin, L: thickness of fiber bundle.

[0133] In order to calculate the average penetration velocity V of the above fiber bundle o , preferably, first calculate the effective viscosity μ eff and vertical permeability K y , the above effective viscosity μ eff and vertical permeability K y It can be calculated according to the following mathematical formulas 2 and 3. At this time, A and B in the custom parameters may change according to the filling form between the fiber units.

[0134] [Mathematical formula 2]

[0135]

[0136]

[0137] μ0: zero shear rate viscosity of the resin, Φ max / Φ: relative volume fraction of fiber bundles, Custom parameters, A, B: constants.

[0138] [Mathematical formula 3]

[0139]

[0140]

[0141] Φ max / Φ: relative volume fraction of fiber bundles, D f : diameter of fiber unit, a: constant.

[0142] The effective viscosity is the viscosity expressed by the power law coefficient of the shear thinning phenomenon of the thermoplastic resin, non-Newtonian resin or non-Newtonian fluid. The vertical permeability K is y It refers to the degree of resin penetration in the thickness direction of the fiber bundle 200.

[0143] The greater the porosity of the fiber bundle, the higher the vertical permeability K of the above resin. y Can have larger values.

[0144] In order to make the process more efficient, when the calculated penetration time exceeds a specific value, the porosity of the fiber bundle may be adjusted so that the penetration time is below the specific value.

[0145] Therefore, the method for manufacturing a long fiber composite material according to an embodiment of the present invention is an easier method for controlling the porosity of the fiber bundle, and the above-mentioned penetration time can be adjusted to be below a preset value according to the types of resin and fiber bundle.

[0146] On the other hand, in the impregnation step, the resin 100 supplied to the container 10 may pass between the plurality of rollers 20 and may penetrate into the fiber bundle 200 .

[0147] At this time, the rollers may include a first roller and a second roller spaced apart from each other, and the resin 100 supplied into the container 10 according to a preset pressure passes between the first roller and the second roller and may penetrate into the fiber bundle.

[0148] In addition, the amount of the resin 100 that penetrates into the fiber bundle 200 can be adjusted. For example, the amount of resin that penetrates through the first roller can be adjusted by a resin knife 50 located at the fiber bundle input portion of the first roller, thereby partially impregnating the fiber bundle.

[0149] In addition, the fiber bundle 200 may be located on the first roller and the second roller. At this time, when the first roller and the second roller rotate, the resin 100 supplied to the inside of the container 10 through the first roller and the second roller is pulled to the fiber bundle 200 located on the first roller and the second roller, thereby being able to penetrate into the fiber bundle 200.

[0150] Hereinafter, the present invention will be described in detail through examples and experimental examples.

[0151] However, the following examples and experimental examples are only for illustrating the present invention, and the contents of the present invention are not limited to the following examples.

[0152] The following Tables 1 to 4 are tables showing the process conditions in the following Examples 1 to 702.

[0153]

Table 1

[0154]

[0155]

Table 2

[0156]

[0157]

Table 3

[0158]

[0159]

Table 4

[0160]

[0161] Example 1

[0162] In order to confirm the penetration time of the resin in the method for producing the long fiber composite material according to the embodiment of the present invention, the following simulation was performed.

[0163] Step 1: Set the permeation pressure ΔP of the resin to 0.5 atm.

[0164] At this time, the resin used was a polypropylene resin which has a zero shear rate viscosity μ0 of 273 Pa·s and a power law coefficient n of 0.3 and is a power law non-Newtonian resin.

[0165] Step 2: Set to thousands of diameters D f The fiber units of 20 μm are bundled into a glass fiber bundle 200 at 2400 tex, and after being spread out to have a width of 24 mm, they are moved toward the lead-out portion 30 .

[0166] Step 3: Set and adjust the distance between the fiber units so that the porosity of the glass fiber bundle is is 0.15, and a penetration pressure of 0.5 atm is applied to the above-mentioned polypropylene resin to make it penetrate into the interior of the glass fiber bundle.

[0167] Embodiment 2-9

[0168] In the above-mentioned Example 1, simulation was performed by the same method as that of the above-mentioned Example 1 except that the porosity was changed to 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 and 0.9, respectively.

[0169] Examples 10-18

[0170] In the above-mentioned Example 1, simulation was performed using the same method as that of the above-mentioned Example 1 except that the width of the glass fiber bundle 200 was changed to 12 mm and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 and 0.9 respectively.

[0171] Examples 19-27

[0172] In the above-mentioned Example 1, simulation was performed using the same method as that of the above-mentioned Example 1 except that the zero shear rate viscosity μ0 was changed to 100 and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 and 0.9, respectively.

[0173] Examples 28-36

[0174] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the zero shear rate viscosity μ0 was changed to 100, the width of the glass fiber bundle 200 was changed to 12 mm, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 and 0.9 respectively.

[0175] Examples 37-45

[0176] In the above-mentioned Example 1, simulation was performed using the same method as that of the above-mentioned Example 1 except that the zero shear rate viscosity μ0 was changed to 50 and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 and 0.9, respectively.

[0177] Examples 46-54

[0178] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the zero shear rate viscosity μ0 was changed to 50, the width of the glass fiber bundle 200 was changed to 12 mm, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0179] Examples 55-63

[0180] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the zero shear rate viscosity μ0 was changed to 50, the osmotic pressure ΔP was changed to 1.0, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0181] Examples 64-72

[0182] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 50, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0183] Examples 73-81

[0184] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the zero shear rate viscosity μ0 was changed to 100, the osmotic pressure ΔP was changed to 1.0, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0185] Examples 82-90

[0186] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 100, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0187] Examples 91-99

[0188] In the above-mentioned Example 1, simulation was performed by the same method as that of the above-mentioned Example 1 except that the permeation pressure ΔP was changed to 1.0 and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0189] Examples 100-108

[0190] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the penetration pressure ΔP was changed to 1.0, the width of the glass fiber bundle 200 was changed to 12 mm, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0191] Examples 109-117

[0192] In the above-mentioned Example 1, simulation was performed using the same method as that of the above-mentioned Example 1 except that the power law coefficient n was changed to 0.38 and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0193] Examples 118-126

[0194] In the above-mentioned embodiment 1, the simulation was performed using the same method as the above-mentioned embodiment 1 except that the power law coefficient n was changed to 0.38, the width of the glass fiber bundle 200 was changed to 12 mm, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0195] Examples 127-135

[0196] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the zero shear rate viscosity μ0 was changed to 100, the power law coefficient n was changed to 0.38, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0197] Examples 136-144

[0198] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 100, the power law coefficient n is changed to 0.38, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0199] Examples 145-153

[0200] In the above-mentioned Example 1, except changing the zero shear rate viscosity μ0 to 50, the power law coefficient n to 0.38, and the porosity to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0201] Examples 154-162

[0202] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 50, the power law coefficient n is changed to 0.38, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0203] Examples 163-171

[0204] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the power law coefficient n was changed to 0.38, the osmotic pressure ΔP was changed to 1.0, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0205] Examples 172-180

[0206] In the above-mentioned Example 1, except that the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0207] Examples 181-189

[0208] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 100, the power law coefficient n is changed to 0.38, the osmotic pressure ΔP is changed to 1.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0209] Examples 190-198

[0210] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 100, the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0211] Examples 199-207

[0212] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 50, the power law coefficient n is changed to 0.38, the osmotic pressure ΔP is changed to 1.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0213] Embodiments 208-216

[0214] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 50, the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0215] Examples 217-225

[0216] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the power law coefficient n was changed to 0.38, the osmotic pressure ΔP was changed to 2.0, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0217] Examples 226-234

[0218] In the above-mentioned Example 1, except that the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 2.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0219] Examples 235-243

[0220] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 150, the power law coefficient n is changed to 0.38, the osmotic pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0221] Embodiment 244-252

[0222] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 150, the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0223] Embodiment 253-261

[0224] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 50, the power law coefficient n is changed to 0.38, the osmotic pressure ΔP is changed to 2.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0225] Examples 262-270

[0226] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 50, the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 2.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0227] Examples 271-279

[0228] In the above-mentioned Example 1, the simulation was performed using the same method as the above-mentioned Example 1 except that the power law coefficient n was changed to 0.38, the osmotic pressure ΔP was changed to 3.0, and the porosity was changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, respectively.

[0229] Examples 280-288

[0230] In the above-mentioned Example 1, except that the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0231] Examples 289-297

[0232] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 150, the power law coefficient n is changed to 0.38, the osmotic pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0233] Examples 298-306

[0234] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 150, the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0235] Examples 307-315

[0236] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 100, the power law coefficient n is changed to 0.38, the osmotic pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0237] Examples 316-324

[0238] In the above-mentioned Example 1, except that the zero shear rate viscosity μ0 is changed to 100, the power law coefficient n is changed to 0.38, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0239] Examples 325-333

[0240] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0241] Examples 334-342

[0242] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was performed using the same method as the above-mentioned Example 1.

[0243] Embodiment 343-351

[0244] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 2.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was performed using the same method as the above-mentioned Example 1.

[0245] Examples 352-360

[0246] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 2.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0247] Examples 361-369

[0248] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0249] Examples 370-378

[0250] In the above-mentioned embodiment 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was performed using the same method as the above-mentioned embodiment 1.

[0251] Examples 379-387

[0252] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 1.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0253] Examples 388-396

[0254] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0255] Examples 397-405

[0256] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 2.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was performed using the same method as the above-mentioned Example 1.

[0257] Embodiments 406-414

[0258] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 2.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0259] Embodiments 406-414

[0260] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 2.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0261] Examples 415-423

[0262] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was performed using the same method as the above-mentioned Example 1.

[0263] Examples 424-432

[0264] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 6 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.6 and being a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was performed using the same method as the above-mentioned Example 1.

[0265] Embodiments 433-441

[0266] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin having a zero shear rate viscosity μ0 of 10 Pa·s, a power-law coefficient n of 0.66 and being a power-law non-Newtonian resin, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0267] Embodiments 442-450

[0268] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 10 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0269] Examples 451-459

[0270] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 10 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 1.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0271] Examples 460-468

[0272] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 10 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0273] Examples 469-477

[0274] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 10 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 2.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0275] Examples 478-486

[0276] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 10 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 2.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0277] Examples 487-495

[0278] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin having a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.66 and being a power-law non-Newtonian resin, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation is performed using the same method as the above-mentioned Example 1.

[0279] Examples 496-504

[0280] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0281] Examples 505-513

[0282] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 50 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 1.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0283] Examples 514-522

[0284] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0285] Examples 523-531

[0286] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 50 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 2.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0287] Examples 532-540

[0288] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 2.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0289] Examples 541-549

[0290] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 50 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0291] Examples 550-558

[0292] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 50 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0293] Examples 559-567

[0294] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 100 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0295] Examples 568-576

[0296] In the above-mentioned Example 1, except that the above-mentioned resin is changed to a nylon 12 resin having a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.66 and being a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0297] Examples 577-585

[0298] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 100 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 5.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0299] Examples 586-594

[0300] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 12 resin which has a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 5.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0301] Examples 595-603

[0302] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 66 resin which has a zero shear rate viscosity μ0 of 200 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 1.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0303] Embodiments 604-612

[0304] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 66 resin which has a zero shear rate viscosity μ0 of 200 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0305] Embodiments 613-621

[0306] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 66 resin which has a zero shear rate viscosity μ0 of 200 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0307] Embodiments 622-630

[0308] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 66 resin which has a zero shear rate viscosity μ0 of 200 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0309] Examples 631-639

[0310] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 66 resin which has a zero shear rate viscosity μ0 of 200 Pa·s, a power law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 5.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0311] Embodiments 640-648

[0312] In the above-mentioned Example 1, except that the above-mentioned resin is changed to nylon 66 resin which has a zero shear rate viscosity μ0 of 200 Pa·s, a power-law coefficient n of 0.66 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 5.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively, the simulation was carried out using the same method as the above-mentioned Example 1.

[0313] Examples 649-657

[0314] In the above-mentioned Example 1, except that the above-mentioned resin is changed to polycarbonate which has a zero shear rate viscosity μ0 of 100 Pa·s, a power law coefficient n of 0.9 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 1.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0315] Examples 658-666

[0316] In the above-mentioned Example 1, except that the above-mentioned resin is changed to polycarbonate which has a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.9 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 1.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0317] Embodiment 667-675

[0318] In the above-mentioned Example 1, except that the above-mentioned resin is changed to polycarbonate which has a zero shear rate viscosity μ0 of 100 Pa·s, a power law coefficient n of 0.9 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 3.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0319] Examples 676-684

[0320] In the above-mentioned Example 1, except that the above-mentioned resin is changed to polycarbonate which has a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.9 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 3.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0321] Examples 685-693

[0322] In the above-mentioned Example 1, except that the above-mentioned resin is changed to polycarbonate which has a zero shear rate viscosity μ0 of 100 Pa·s, a power law coefficient n of 0.9 and is a power-law non-Newtonian resin, the permeation pressure ΔP is changed to 5.0, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0323] Examples 694-702

[0324] In the above-mentioned Example 1, except that the above-mentioned resin is changed to polycarbonate which has a zero shear rate viscosity μ0 of 100 Pa·s, a power-law coefficient n of 0.9 and is a power-law non-Newtonian resin, the penetration pressure ΔP is changed to 5.0, the width of the glass fiber bundle 200 is changed to 12 mm, and the porosity is changed to 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The simulation was carried out using the same method as the above-mentioned Example 1.

[0325] Experimental Example 1

[0326] In the method for producing a long fiber composite material according to an embodiment of the present invention, the following experiment was conducted to confirm the penetration time of the resin in the impregnation step.

[0327] In Examples 1 to 702, in step 3 of infiltrating the resin into the interior of the glass fiber bundle, the following mathematical formula 1 is used to measure the time it takes for the resin to 100% fill the pores of the glass fiber bundle and for the porosity of the glass fiber bundle to become 0%, i.e., the complete penetration time, and the results are shown in Tables 5 to 82 below.

[0328] The above-mentioned complete penetration time is within 8 seconds, more preferably within 7 seconds, and further preferably within 6 seconds, and can be regarded as a reference time for designing an impregnation mold.

[0329] [Mathematical formula 1]

[0330]

[0331] V o : Average penetration velocity of fiber bundle, n: Power law coefficient of resin, K y : Vertical permeability, μ eff : effective viscosity, ΔP: penetration pressure of resin, L: thickness of fiber bundle.

[0332]

Table 5

[0333]

[0334]

Table 6

[0335]

[0336] Tables 5 and 6 above are respectively the data of the complete penetration time results when the width of the glass fiber bundle is 24 mm and 12 mm under the conditions that the penetration pressure of the polypropylene resin is 0.5 atmospheres, the zero shear rate viscosity is 273 Pa·s, and the power law coefficient is 0.3. When the width of the glass fiber bundle is 24 mm, it can be seen that when the glass fiber bundle has a porosity of more than 0.4, the penetration time consumed is less than 3.4 seconds, on the contrary, when the porosity is less than 0.3, the penetration time consumed is more than 36 seconds; when the width of the glass fiber bundle is 12 mm, it can be seen that when the glass fiber bundle has a porosity of more than 0.5, the penetration time consumed is less than 1.03 seconds, on the contrary, when the porosity is less than 0.4, the penetration time consumed is more than 6.8 seconds.

[0337]

Table 7

[0338]

[0339]

Table 8

[0340]

[0341] Tables 7 and 8 above are data on the complete penetration time results when the resin penetration pressure is 0.5 atmospheres, the zero shear rate viscosity is 100 Pa·s, the power law coefficient is 0.3, and the width of the glass fiber bundle is 24 mm and 12 m, respectively.

[0342] As shown in Tables 7 and 8 above, it can be seen that when the width of the above-mentioned glass fiber bundle is 24 mm and 12, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is greater than 0.3, it is within 1.27 seconds and 2.65 seconds, respectively.

[0343]

Table 9

[0344]

[0345]

Table 10

[0346]

[0347] Tables 9 and 10 above are the data of the complete penetration time results when the penetration pressure of the polypropylene resin is 0.5 atmospheres, the zero shear rate viscosity is 50 Pa·s, the power law coefficient is 0.3, and the width of the glass fiber bundle is 24 mm and 12 m, respectively.

[0348] As shown in Tables 9 and 10 above, it can be known that when the width of the above-mentioned glass fiber bundle is 24 mm, when the porosity is below 0.15, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is above 0.2, the complete penetration time is 4.9 seconds, which is less than 6 seconds; when the width of the glass fiber bundle is 12, when the porosity is below 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is above 0.3, it is within 0.27 seconds.

[0349]

Table 11

[0350]

[0351]

Table 12

[0352]

[0353] Tables 11 and 12 above are the data of the complete penetration time results when the width of the glass fiber bundle is 24 mm and 12 m, respectively, under the conditions of the penetration pressure of the polypropylene resin being 0.5 atmospheres, the zero shear rate viscosity being 50 Pa·s, and the power law coefficient being 0.3. It can be seen that in both cases, when the porosity is less than 0.15, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is greater than 0.2, the complete penetration time is within 0.49 seconds and 1 second, respectively.

[0354]

Table 13

[0355]

[0356]

Table 14

[0357]

[0358] Tables 13 and 14 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 1.0 atmospheric pressure, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.3. It can be seen that when the width is 24 mm, when the porosity is less than 0.15, the complete penetration time exceeds 6 seconds, on the contrary, when it is greater than 0.2, it is within 4.9 seconds; when the width is 12 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, it is within 0.27 seconds.

[0359]

Table 15

[0360]

[0361]

Table 16

[0362]

[0363] Tables 15 and 16 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm under the conditions that the penetration pressure of the polypropylene resin is 1.0 atmosphere, the zero shear rate viscosity is 273 Pa·s, and the power law coefficient is 0.3. It can be seen that when the width is 24 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, it is within 3.6 seconds; when the width of the glass fiber bundle is 12, it can be seen that when the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, it is within 0.69 seconds.

[0364]

Table 17

[0365]

[0366]

Table 18

[0367]

[0368] Tables 17 and 18 above show the result data when the width of the glass fiber bundle is 24 mm and 12 mm under the conditions of the penetration pressure of the polypropylene resin being 0.5 atmospheres, the zero shear rate viscosity being 273 Pa·s, and the power law coefficient being 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.4, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.5, the complete penetration time is within 3.2 seconds and 6.7 seconds, respectively.

[0369]

Table 19

[0370]

[0371]

Table 20

[0372]

[0373] Tables 19 and 20 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 0.5 atmospheres, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.3, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.4, the complete penetration time is within 1.1 seconds and 2.3 seconds, respectively.

[0374]

Table 21

[0375]

[0376]

Table 22

[0377]

[0378] Tables 21 and 22 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 0.5 atmospheres, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.2, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.3, the complete penetration time is within 1.32 seconds and 2.72 seconds, respectively.

[0379]

Table 23

[0380]

[0381]

Table 24

[0382]

[0383] Tables 23 and 24 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 1.0 atmosphere, the zero shear rate viscosity is 273 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.3, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.4, the complete penetration time is within 2.5 seconds and 5.2 seconds, respectively.

[0384]

Table 25

[0385]

[0386]

Table 26

[0387]

[0388] Tables 25 and 26 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 1.0 atmosphere, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.2, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.3, the complete penetration time is within 1.32 seconds and 2.73 seconds, respectively.

[0389]

Table 27

[0390]

[0391]

Table 28

[0392]

[0393] Tables 27 and 28 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 1.0 atmosphere, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm, when the porosity is less than 0.15, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.2, it is within 4.7 seconds; when the width is 12 mm, it can be seen that when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, the complete penetration time is within 0.44 seconds.

[0394]

Table 29

[0395]

[0396]

Table 30

[0397]

[0398] Tables 29 and 30 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 2.0 atmospheres, the zero shear rate viscosity is 273 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, the complete penetration time is within 3.0 seconds; when the width of the glass fiber bundle is 12 mm, it can be seen that when the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, the complete penetration time is within 0.84 seconds.

[0399]

Table 31

[0400]

[0401]

Table 32

[0402]

[0403] Tables 31 and 32 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 3.0 atmospheres, the zero shear rate viscosity is 150 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm, when the porosity is less than 0.15, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.2, the complete penetration time is within 4.6 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, the complete penetration time is within 0.44 seconds.

[0404]

Table 33

[0405]

[0406]

Table 34

[0407]

[0408] Tables 33 and 34 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 2.0 atmospheres, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.15, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.2, the complete penetration time is within 0.75 seconds and 1.6 seconds, respectively.

[0409]

Table 35

[0410]

[0411]

Table 36

[0412]

[0413] Tables 35 and 36 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm under the conditions of the penetration pressure of the polypropylene resin being 3.0 atmospheres, the zero shear rate viscosity being 273 Pa·s, and the power law coefficient being 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.2, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.3, the complete penetration time is within 1.1 seconds and 2.2 seconds, respectively.

[0414]

Table 37

[0415]

[0416]

Table 38

[0417]

[0418] Tables 37 and 38 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polypropylene resin is 3.0 atmospheres, the zero shear rate viscosity is 150 Pa·s, and the power law coefficient is 0.38. It can be seen that when the width is 24 mm, when the porosity is less than 0.15, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.2, it is less than 4.6 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, the complete penetration time is within 0.44 seconds.

[0419]

Table 39

[0420]

[0421]

Table 40

[0422]

[0423] The above Tables 39 and 40 are the result data when the width of the glass fiber bundle is 24 mm and 12 mm under the conditions of the penetration pressure of the polypropylene resin being 3.0 atmospheres, the zero shear rate viscosity being 100 Pa·s, and the power law coefficient being 0.38. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.15, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.2, the complete penetration time is within 1.6 seconds and 3.3 seconds respectively.

[0424]

Table 41

[0425]

[0426]

Table 42

[0427]

[0428] Tables 41 and 42 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 6 resin is 0.5 atmospheres, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.6. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.4, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.5, the complete penetration time is within 2.5 seconds and 5.1 seconds, respectively.

[0429]

Table 43

[0430]

[0431]

Table 44

[0432]

[0433] Tables 43 and 44 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 6 resin is 2.0 atmospheres, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.6. It can be seen that when the width is 24 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, the complete penetration time is within 3.3 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, the complete penetration time is within 1.6 seconds.

[0434]

Table 45

[0435]

[0436]

Table 46

[0437]

[0438] Tables 45 and 46 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 6 resin is 0.5 atmospheres, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.6. It can be seen that when the width is 24 mm, when the porosity is less than 0.5, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.6, the complete penetration time is within 3.1 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.6, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.7, the complete penetration time is within 2.7 seconds.

[0439]

Table 47

[0440]

[0441]

Table 48

[0442]

[0443] Tables 47 and 48 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 6 resin is 1.0 atmospheric pressure, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.6. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.4, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.5, the complete penetration time is within 2.5 seconds and 5.1 seconds, respectively.

[0444]

Table 49

[0445]

[0446]

Table 50

[0447]

[0448] Tables 49 and 50 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 6 resin is 2.0 atmospheres, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.6. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.3, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.4, the complete penetration time is within 2.4 seconds and 5.0 seconds, respectively.

[0449]

Table 51

[0450]

[0451]

Table 52

[0452]

[0453] Tables 51 and 52 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 6 resin is 3.0 atmospheres, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.6. It can be seen that when the width is 24 mm, the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, it is less than 5.2 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, the complete penetration time is within 2.52 seconds.

[0454]

Table 53

[0455]

[0456]

Table 54

[0457]

[0458] Tables 53 and 54 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 12 resin is 0.5 atmospheres, the zero shear rate viscosity is 10 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm, the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, it is more than 4.7 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, the complete penetration time is within 2.5 seconds.

[0459]

Table 55

[0460]

[0461]

Table 56

[0462]

[0463] Tables 55 and 56 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm under the conditions that the penetration pressure of nylon 12 resin is 1.0 atmospheric pressure, the zero shear rate viscosity is 10 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.2, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.3, the complete penetration time is within 1.7 seconds and 3.41 seconds, respectively.

[0464]

Table 57

[0465]

[0466]

Table 58

[0467]

[0468] Tables 57 and 58 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 12 resin is 2.0 atmospheres, the zero shear rate viscosity is 10 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm, the porosity is less than 0.15, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.2, it is within 5.03 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, the complete penetration time is within 1.2 seconds.

[0469]

Table 59

[0470]

[0471]

Table 60

[0472]

[0473] Tables 59 and 60 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions of the penetration pressure of nylon 12 resin being 0.5 atmospheres, the zero shear rate viscosity being 50 Pa·s, and the power law coefficient being 0.66. It can be seen that when the porosity is below 0.4, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is above 0.5, the complete penetration time is within 4.8 seconds; it can be seen that when the width is 12 mm, when the porosity is below 0.5, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is above 0.6, the complete penetration time is within 4.11 seconds.

[0474]

Table 61

[0475]

[0476]

Table 62

[0477]

[0478] Tables 61 and 62 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 12 resin is 1.0 atmospheric pressure, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm, the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, the complete penetration time is within 4.75 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.4, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.5, the complete penetration time is within 3.5 seconds.

[0479]

Table 63

[0480]

[0481]

Table 64

[0482]

[0483] Tables 63 and 64 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm under the conditions that the penetration pressure of nylon 12 resin is 2.0 atmospheres, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.3, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.4, the complete penetration time is within 1.66 seconds and 3.45 seconds, respectively.

[0484]

Table 65

[0485]

[0486]

Table 66

[0487]

[0488] Tables 65 and 66 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 12 resin is 3.0 atmospheres, the zero shear rate viscosity is 50 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm, when the porosity is less than 0.2, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.3, the complete penetration time is within 3.55 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, the complete penetration time is within 1.87 seconds.

[0489]

Table 67

[0490]

[0491]

Table 68

[0492]

[0493] Tables 67 and 68 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 12 resin is 3.0 atmospheres, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.3, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.4, the complete penetration time is within 2.57 seconds and 5.34 seconds, respectively.

[0494]

Table 69

[0495]

[0496]

Table 70

[0497]

[0498] Tables 69 and 70 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions of the penetration pressure of nylon 12 resin being 5.0 atmospheres, the zero shear rate viscosity being 100 Pa·s, and the power law coefficient being 0.66. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.3, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.4, the complete penetration time is within 1.66 seconds and 3.45 seconds, respectively.

[0499]

Table 71

[0500]

[0501]

Table 72

[0502] Tables 71 and 72 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 66 resin is 1.0 atmospheric pressure, the zero shear rate viscosity is 200 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 12 mm, when the porosity is less than 0.5, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.6, the complete penetration time is within 5.69 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.6, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.7, the complete penetration time is within 5.42 seconds.

[0503]

Table 73

[0504]

[0505]

Table 74

[0506]

[0507] Tables 73 and 74 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 66 resin is 3.0 atmospheres, the zero shear rate viscosity is 200 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm and 12 mm, when the porosity is both below 0.4, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.5, the complete penetration time is within 2.58 seconds and 5.34 seconds, respectively.

[0508]

Table 75

[0509]

[0510]

Table 76

[0511]

[0512] Tables 75 and 76 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of nylon 66 resin is 5.0 atmospheres, the zero shear rate viscosity is 200 Pa·s, and the power law coefficient is 0.66. It can be seen that when the width is 24 mm, the porosity is less than 0.3, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.4, the complete penetration time is within 3.39 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.4, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.5, the complete penetration time is within 2.46 seconds.

[0513]

Table 77

[0514]

[0515]

Table 78

[0516]

[0517] Tables 77 and 78 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polycarbonate resin is 1.0 atmosphere, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.9. It can be seen that when the width is 24 mm, when the porosity is below 0.7, the complete penetration time exceeds 6 seconds. On the contrary, when the porosity is above 0.8, the complete penetration time is within 4.8 seconds; it can be seen that when the width is 12 mm, when the porosity is below 0.9, the complete penetration time exceeds 6 seconds.

[0518]

Table 79

[0519]

[0520]

Table 80

[0521]

[0522] Tables 79 and 80 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polycarbonate resin is 3.0 atmospheres, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.9. It can be seen that when the width is 24 mm, the porosity is less than 0.5, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.6, the complete penetration time is within 4.09 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.6, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is greater than 0.7, the complete penetration time is within 4.71 seconds.

[0523]

Table 81

[0524]

[0525]

Table 82

[0526]

[0527] Tables 81 and 82 above are the result data when the width of the glass fiber bundle is 24 mm and 12 mm, respectively, under the conditions that the penetration pressure of the polycarbonate resin is 5.0 atmospheres, the zero shear rate viscosity is 100 Pa·s, and the power law coefficient is 0.9. It can be seen that when the width is 24 mm, the porosity is less than 0.4, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is above 0.5, the complete penetration time is within 4.63 seconds; it can be seen that when the width is 12 mm, when the porosity is less than 0.5, the complete penetration time exceeds 6 seconds, on the contrary, when the porosity is above 0.6, the complete penetration time is within 4.79 seconds.

Claims

1. A method for manufacturing a long fiber composite material, using a long fiber composite material manufacturing device, the manufacturing device comprising: A container (10) for containing the resin (100); a roller (20) disposed inside the container (10) and rotating in one direction, the roller (20) comprising a first roller and a second roller spaced apart from each other; a lead-out portion (30) for applying tension to the fiber bundle (200) and moving the fiber bundle (200) in one direction, the fiber bundle (200) having porosity; and a resin supply portion (40) disposed at a lower portion of the container (10) and supplying the resin (100) to the inside of the container (10), The manufacturing method comprises: a supplying step, wherein the resin supplying portion (40) supplies the resin (100) from the lower portion of the container (10) to the interior of the container (10) at a preset pressure; a moving step, wherein the fiber bundle (200) on the roller (20) is moved in one direction by the lead-out portion (30); an impregnation step, wherein the resin (100) supplied to the interior of the container (10) is infiltrated into the pores of the fiber bundle (200); wherein, by the rotation of the first roller and the second roller, the resin (100) is pulled to the fiber bundle (200) located on the first roller and the second roller, so that the resin (100) is infiltrated into the interior of the fiber bundle (200), By adjusting the amount of the resin (100) that penetrates through the first roller, only one surface of the fiber bundle (200) is brought into contact with the resin (100), thereby partially impregnating the fiber bundle. Wherein, the impregnation step is controlled according to the following mathematical formula 1; [Mathematical formula 1] V o : Average penetration velocity of fiber bundle, n: Power law coefficient of resin, K y : Vertical permeability, μ eff : effective viscosity, ΔP: penetration pressure of resin, L: thickness of fiber bundle.

2. The method for producing a long fiber composite material according to claim 1, characterized in that: The impregnation step comprises: A porosity control step is to control the porosity of the fiber bundle (200) so that the penetration time required for the resin (100) to fill the internal pores of the fiber bundle (200) is less than a preset time.

3. The method for producing a long fiber composite material according to claim 2, characterized in that: The porosity control step comprises: A step of controlling the distance between each fiber unit contained in the fiber bundle (200).

4. The method for producing a long fiber composite material according to claim 3, characterized in that: The step of controlling the distance between each fiber unit contained in the fiber bundle is performed by applying a force to the fiber bundle (200) in a direction perpendicular to a direction in which tension is applied.

5. The method for producing a long fiber composite material according to claim 3, characterized in that: The step of controlling the distance between each fiber unit included in the fiber bundle (200) is performed by adjusting the amount of the resin (100) permeated into the fiber bundle (200).

6. The method for producing a long fiber composite material according to claim 1, characterized in that: In the impregnation step, The resin (100) supplied into the container (10) according to a preset pressure passes between the first roller and the second roller and penetrates into the interior of the fiber bundle (200).

7. The method for producing a long fiber composite material according to claim 1, characterized in that: The preset pressure is 0.3 to 5.5 atmospheres.

8. The method for producing a long fiber composite material according to claim 1, characterized in that: The resin (100) is a non-Newtonian resin having a power law coefficient of 0.25 to 0.

92.

9. The method for producing a long fiber composite material according to claim 8, characterized in that: The non-Newtonian resin comprises: At least one of maleic anhydride, acrylic acid, amine, ester, epoxy and chemically bonded compounds thereof.

10. The method for producing a long fiber composite material according to claim 8, characterized in that: The non-Newtonian resin comprises: At least one of polypropylene resin, nylon resin, polyethylene resin, polybutylene terephthalate resin, polyethylene terephthalate resin, polyvinyl chloride resin and mixed resins thereof.

11. The method for producing a long fiber composite material according to claim 1, characterized in that: The resin (100) is dispersed with nanoparticles.

12. The method for producing a long fiber composite material according to claim 11, characterized in that: The nanoparticles include at least one of nanoclay particles, cellulose nanofiber particles, carbon nanoparticles, zinc sulfide nanoparticles and silver nanoparticles.

13. The method for producing a long fiber composite material according to claim 1, characterized in that: The fiber bundle (200) is at least one of glass fiber filaments, carbon fiber filaments, basalt fiber filaments, aramid fiber filaments, spectrum fiber filaments, natural fiber filaments, and mixed filaments thereof.

14. The method for producing a long fiber composite material according to claim 1, characterized in that: The long fiber composite material has thermoplasticity.

Citation Information

Patent Citations

  • Preparation of fiber reinforced resin structure

    JP1985240435A

  • Fibre-reinforced plastic material

    EP2329937A1

  • Device and method for manufacturing fiber-reinforced thermoplastic resin tape

    EP3338979A1

  • Apparatus for impregnating continuously individual filaments of fiber bundle with resin

    KR1020090069682A